IFRS 17 and its effects on financial performance and the statement of financial position: a comparative analysis of the South African insurance companies including banks - Myendeki, Sive (College of Accounting, 2026)
In the South African market, insurance plays an important role by enabling businesses to manage risks they could not manage individually, while also reinvesting some of the premiums in South Africa to drive economic growth and create jobs. For individuals, insurance provides important protection for valuable assets. The introduction of International Financial Reporting Standards (IFRS) 17 by the International Accounting Standards Board (IASB), effective from 1 January 2023, resulted in a change in the measurement requirements of insurance contracts compared to IFRS 4. This study investigated the impact of the transition from IFRS 4 to IFRS 17 on the financial performance and the statement of financial position of insurance service providers in South Africa. This study, grounded in the Rational Choice Theory, the Liquidity Preference Theory and the Pecking Order Theory, analysed twelve insurance service providers licensed by the FSCA and operating in South Africa. The results of the study revealed that IFRS 17 did not have a statistically significant impact on the financial performance of these insurance service providers. However, the statement of financial position experienced a statistically significant decrease in reported total assets and total liabilities, while the changes to the reported equity and insurance liabilities were not found to be statistically significant. The decrease in the reported total assets and liabilities was noted to be due to the change in the measurement requirements for insurance contracts accounting such as the treatment of acquisition costs. Under IFRS 4, insurers were allowed to capitalise and defer acquisition costs as deferred acquisition cost assets on the balance sheet. The DAC asset was then expensed to the income statement over the life of the insurance contract. However, under IFRS 17, this DAC is included as part of the insurance service liability resulting in a decrease in reported total assets and total liabilities. Furthermore, the reported total assets and liabilities are impacted by the requirement to discount these balances using the IFRS 17 risk-adjusted approaches as well as the changes to the underlying assumption used in the measurement calculations. This analysis and results may assist regulators, investors and other users of financial statements to better understand the impact IFRS 17 has had on the financial performance of insurance service providers in South Africa.